Representações sociais de solo e educação ambiental nas séries iniciais do ensino fundamental em Pato Branco - PR - Favarim, Ligiane Corso (2012)
Recognizing the importance that the soil has in maintaining ecosystems, becomes essential that this issue be worked in the environmental context by the elementary education institutions, taking into account the knowledge students already possess interrelating them to scientific knowledge. Thus, the present study aimed to identify the social representations of soil by teachers of initial grades of elementary school in the city of Pato Branco - PR, trying to relate them to pedagogical practice in soils and environmental education. To achieve the research objectives, methodology was based on the use of questionnaires, analysis of education allowances (planning and textbook) and conducting focus groups. The results presented by the research indicated that there are failures and misconceptions in education allowances, not agreeing with what is proposed by the National Curriculum Standards of Natural Sciences and Environment. Regarding the social representation of soil and environmental education, identified through questionnaires and focus group, it was found that there is difference between the representations of teachers, resulting in the formation of two distinct groups. The group of the rural area has presented characteristics of involvement with the ground in the context of environmental oriented preservation issues for planting and harvesting, which demonstrates a strong relationship of survival established by them in relation to the soil and the environment. Teachers from the central and peripheral area has indicated that the soil is a natural resource for human use. These indications have strong influence on the way that each of these groups perceive and use the soil in your social and community life. It was identified that the social representation of teachers influences the teaching practice, ie, , in the way they conduct their activities and valorize this natural resource. Overall, teachers expressed having difficulty in understanding the soil and teach it consistently, considering they have expressed little knowledge to develop this theme together with the environmental context.